Enhancing surface integrity of additively manufactured inconel 718 by roller burnishing process - KAYNAK, YUSUF (My University, 2022)
© 2022 The Author(s).This work presents the effect of burnishing process including burnishing force, burnishing speed and burnishing conditions on surface properties of Inconel 718 alloy fabricated by laser powder based fusion additive manufacturing. As-built, sand blasted and heat-treated specimens are burnished and final surface properties such as surface roughness, surface topography, and microhardness are presented. The performance of the burnished surface is tested through wear test. This study reveals that burnishing process makes substantial contribution to reduce surface roughness of additively manufactured Inconel 718 alloy. Moreover, surface hardness is notably increased resulting from burnishing process and hence wear resistance of this alloy improved. Wear resistance of as-built specimens was increased by 38% through implementing roller burnishing. Wear resistance of heat-treated specimens is increased by 55% through implementing roller burnishing process.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; ENGINEERING, MANUFACTURING; Fizik Bilimleri; Endüstri ve İmalat Mühendisliği; Control and Systems Engineering; Physical Sciences; Industrial and Manufacturing Engineering; Additive manufacturing; Burnishing process; Inconel 718; Surface integrity